2022
DOI: 10.1002/suco.202100651
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study, modeling, and reliability analysis of impact resistance of micro steel fiber‐reinforced concrete modified with nano silica

Abstract: This paper presents the experimental, statistical modeling, and reliability analysis of impact resistance of micro steel fiber reinforced concrete (FRC) incorporated with nano silica (NS) using a drop-weight impact test. U-shaped concrete specimens were developed for the experimental work. The result showed that the combined effect of micro steel fiber (SF) and NS led to significant improvement of impact resistance of concrete mixtures, and lower ductility ratios were obtained for specimens with high SF and NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…The Eq. ( 4) and ( 5) assess the response of the model with both linear and nonlinear independent variables [27] [28].…”
Section: Response Surface Methodologymentioning
confidence: 99%
“…The Eq. ( 4) and ( 5) assess the response of the model with both linear and nonlinear independent variables [27] [28].…”
Section: Response Surface Methodologymentioning
confidence: 99%
“…The number of impacting blows at the failure stage was recorded as the ultimate strength (N U ). During drop-weight impact testing, the U-shaped specimen's impact energy was determined from the potential energy of the falling weight [43,50]. The energy absorption capacities of the test specimens for the number of blows (N) and falling hammer (m) released from the fixed height (h) corresponding to the specified cracking strengths were evaluated using Equation ( 1)…”
Section: Drop-weight Impact Test Of Pupcmentioning
confidence: 99%
“…The factors responsible for these variations are as follows: (i) During the test, cracks can occur anywhere and in any direction on the cylinder specimen adopted in this impact testing procedure; and (ii) Any failure modes are considered in the test, contributing to the dispersed result. For this reason, the current study adopted a U-shaped specimen, as found in the literature [40][41][42][43] to minimize the drop-weight impact test result variations by restraining the crack formation, which is expected to occur in a predetermined position. Many studies have been conducted to study the potential uses of polyurethane for strengthening and retrofitting to improve structures' impact resistance [28,31,33].…”
Section: Introductionmentioning
confidence: 99%
“…The failure mode of the SSC mixture is continuous. The following assumptions can be made 53,54 : (1) SSA and natural aggregate were evenly distributed in concrete.…”
Section: Development Of Damage Modelmentioning
confidence: 99%
“…The failure mode of the SSC mixture is continuous. The following assumptions can be made 53,54 : (1) SSA and natural aggregate were evenly distributed in concrete. (2) Under the compression test, the SSC mixtures damage was initially originated in the ITZ of SSA and cement paste, followed by the appearance of damage in the ITZ of natural aggregate and cement particles.…”
Section: Damage Modelmentioning
confidence: 99%